DINAMIKA RESILIENSI ORANG TUA ANAK AUTIS - Siti Mumun Muniroh (IAIN Pekalongan, 2010)
This research is meant to know the dynamic of resiliency of the parents who have autism child in Pekalongan City by using phenomenology theory. To collect data it was used in-depth interview and observation. The respondents are the parents who have autism child that goes to extraordinary school for disable persons YRI of Pekalongan City. The result of this research shows that the forming of the parents’ resiliency is influenced by internal and external factors. Cognitively, at the beginning of diagnose, the parents feel worry, stress, and even think to blame on themselves. Affectively, worry, confuse and sad feeling are experienced by them. After adaptation and meaning process, cognitive and affective conditions of them begin to change. They view the problems more positive, and have been able to accept and broad minded the problems faced by them, so that they are motivated to find the solution for their children